THE EVALUATION OF ENGLISH TEXTBOOK FOR GRADE VII OF JUNIOR HIGH SCHOOL IN INDONESIA - Sri Handayani (Universitas Negeri Padang, 2016)
The purpose of this research was to evaluate the quality of English textbook for grade VII of junior high school in Indonesia entitled “When English Rings a Bell - Revised Edition”. This research employed a document analysis (Cresswel, 2012). The evaluation of the textbook was conducted qualitatively through adapted checklist developed by Litz (2005). The checklist was six criteria including practical consideration, layout and design, activities, skills, language type, subject and content, out of seven criteria in Litz’s checklist were selected for this research.The results of this research revealed that the “When English Rings a Bell - Revised Edition” textbook fits the criteria of good English textbook in term of practical consideration, layout and design, activities, and skills. However, this textbook needs to provide workbook and audio-tapes as supporting aids, detailed overview instead of general overview, grammar points and vocabulary items, and highlights and practices natural pronunciation. In term of language types this textbook needs many improvement or revision, such as there are no authentic, i.e. real-life English language used, there are no brief and easy example and explanation of grammar, and there are no language represents a diverse range of registers and accents. And in terms of subject and content, this textbook needs to improve the variety in the subject and content of the textbook in order to make this textbook interesting, challenging and motivating.